Pengaruh Retailing Mix dan Service Quality Terhadap Purchase Decision pada PT Akur Pratama (Toserba Yogya) Sukabumi - Ade Munhiar; Zulfa Jalillah (Institut Manajemen Wiyata Indonesia, 2018)
This study aims to determine : the effect of retailing mix on purchase decision, the effect of service quality on purchase decision, and the influence of retailing mix and service quality simultaneously on purchase decision. The subjects of this study are customers who visited and purchases products to Yogya Department Store Sukabumi with a total of 100 respondents. Methods of data collection through surveys by using questionnaires. Data analysis techniques used in this study are validity test, reliability test, classical assumption test and hypothesis test. The results of this study indicate that (1) retailing influences partially and significantly on the purchase decision with value (3,847> 1,9847), (2) service quality has a partial and significant effect on the purchase decision with value (5,466> 1,9847), (3) retailing mix and service quality simultaneously have a positive and significant effect on purchase decision with value (64,811> 3,94). Further research is needed by the company, increasing pricing, marketing and responsiveness in service to consumers.